2010
DOI: 10.3109/09553001003734519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2.45 mT sinusoidal 50 Hz magnetic field onSaccharomyces cerevisiaestrains deficient in DNA strand breaks repair

Abstract: The data presented in the current report show that the applied MF (2.45 mT, sinusoidal 50 Hz, 96 h) induces alterations in the growth and survival of S. cerevisiae strains deficient in DNA strand breaks repair. In contrast, the MF treatment does not induce alterations in the cell cycle and does not cause DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Controversial data have been published concerning the enhancement [31,61], inhibition [62,63] or non-effect of MF exposure with respect to cell proliferation [64,65]. Nevertheless, the scientific contribution of Pasche’s lab seems to be clarifying the potential role of EMFs in proliferation rate control.…”
Section: Biological Effects Of Emfsmentioning
confidence: 99%
“…Controversial data have been published concerning the enhancement [31,61], inhibition [62,63] or non-effect of MF exposure with respect to cell proliferation [64,65]. Nevertheless, the scientific contribution of Pasche’s lab seems to be clarifying the potential role of EMFs in proliferation rate control.…”
Section: Biological Effects Of Emfsmentioning
confidence: 99%
“…Even though a number of studies have reported DNA damage effects from ELF-MFs, the overall results remain inconclusive [9,10,[15][16][17][18][19]. The main reason for this inconsistency was the use of different cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews of in vivo and in vitro laboratory studies on ELF-MF [1][2][3][4][5][6] have indicated contradictory results from genotoxic endpoints, such as chromosome aberrations, micronuclei, sister chromatid exchange, and DNA strand breakage. These results included increased DNA damage by ELF-MF under specific in vitro and in vivo conditions [7,8], yet no such effects were reported in the other studies [9]. These inconsistent experimental data may be due to the differences in the equipment used to generate magnetic fields, exposure protocols, and biological materials, such as cell lines, animal species, strain, and age.…”
Section: Introductionmentioning
confidence: 99%
“…It is preferred to induce an error rather than not repair the damage, in order to guarantee the stability of the genome and cell viability [ 7 ]. In S. cerevisiae , the role of HR in DSB repair predominates [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%